An Image Encryption Scheme Using 2D Generalized Sawtooth Maps - Ye, Ruisong; Yu, Wenping (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In this paper, a new image encryption scheme based on 2D generalized sawtooth map is proposed. Utilizing the chaotic nature of 2D generalized sawtooth maps, image pixel positions are scrambled and image pixels gray values are changed to encrypt the plain-images. Experimental results have been carried out with detailed analysis to demonstrate that the proposed image encryption scheme possesses large key space to resist brute-force attack and possesses good statistical properties to frustrate statistical analysis attacks.